Improving Students’ Ability in Creating Karawo Design Trought the Project-Based Learning Model in Class IV at SDN 5 Tilongkabila - Siti Nurdiah Derbang; Mimy Astuty Pulukadang; Nurainun; La Ode Karlan; Wiwy Triyanty Pulukadang (Jurnal Kiprah Pendidikan, 2026)
This study aimed to improve fourth-grade students' ability to create Karawo designs through the implementation of the Project-Based Learning (PjBL) model at SDN 5 Tilongkabila, Bone Bolango Regency, Indonesia. This study employed a Classroom Action Research (CAR) design conducted in two cycles involving 13 fourth-grade students as the research participants. The preliminary observation revealed that students' ability to create Karawo designs was relatively low because the learning process primarily focused on coloring pre-prepared patterns rather than encouraging students to develop their own designs. Data were collected through classroom observation, performance assessment, interviews, and documentation. Students' performance was assessed based on four artistic design principles: unity, proportion, rhythm, and harmony. The findings indicated a progressive improvement in students' performance across the action cycles. In the first meeting of Cycle I, only 3 students (23%) achieved the predetermined competency criteria. This number increased to 6 students (46%) in the second meeting of Cycle I and further improved to 11 students (85%) in Cycle II, exceeding the predetermined success indicator of 75%. These findings indicate that the implementation of the Project-Based Learning (PjBL) model improved the ability to create Karawo designs among fourth-grade students at SDN 5 Tilongkabila, Bone Bolango Regency